Crimes in the 19th Century London in Charles Dickens’ Oliver Twist (Language Circle: Journal of Language and Literature, 2019)
The world of literature is the result of human’s culture, where it can be the expression of one’s life experience which is influenced by a certain society of certain period. Practically, literature can sometimes help readers in understanding the condition of the society. Charles Dickens’ Oliver Twist as one of literary works that contains culture and life of Victorian era has described clearly about all the things that is going on in the 19th century of London. The novel satirizes the poor living condition, unemployment, poverty, and social class at that time. It also attacts the Poor Law Amendment Act of 1834 and the workhouse system that causes suffer to the poor and increases crime. Using sociological approach as one of the study that learns about the social condition of certain culture, Crimes in the 19th Century London in Charles Dickens’ Oliver Twist is chosen as the title of the study is to find out the kinds of crimes exist in London and the causing factors that increase the number of crimes. The result of the study shows that the kind of crime exists in the 19th century of London as shown in Oliver Twist is pick-pocketing, thievery, robbery, burglary, house-breaking, and murder. While the causing factors that increase crime are unemployment and poverty, Poor Law Amendment Act of 1834 and the workhouse, and social class and social gap.